Radiation reaction and renormalization for a photon-like charged particle - Yaremko, Yu. (Вопросы атомной науки и техники, 2007)
A renormalization scheme which relies on energy-momentum and angular momentum balance equations is applied to the derivation of effective equation of motion for a massless point-like charge. Unlike the massive case, the rates of radiated energy-momentum and angular momentum tend to infinity whenever the massless source is accelerated. The external electromagnetic fields which do not change the velocity of the particle admit only its presence within the interaction area. The effective equation of motion is the equation on eigenvalues and eigenvectors of the electromagnetic tensor. The same solution arises in Rylov's model of magnetosphere of a rapidly rotating neutron star (pulsar).